2017
DOI: 10.1155/2017/5924717
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of a Cationic Guanidine Compound against Two Pathogenic Oral Bacteria

Abstract: This study evaluated the potential antimicrobial properties of a polyguanidine (CatDex) on two oral bacteria. Chlorhexidine gluconate 1340 μmoL L−1 (CHX 0.12%) was used as control. Streptococcus mutans (S. mutans) and Porphyromonas gingivalis (P. gingivalis) were grown in BHI media. Bacterial sensitivity and antimicrobial activity were determined by the minimum inhibitory concentration (MIC) and Kirby-Bauer methods. To study side effects, that is, toxicity, dental pulp stem cells (DPSCs) were used. Fluorometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…The observed effect of inhibition of biofouling in the case of DNDamine coating seems to have the same mechanism as that observed for polycationic polymers -guanidine derivatives, which are known antiseptic agents [42][43][44]. In the case of the latter, close contact of a substance with a high density of positively charged groups with cell walls…”
Section: Discussionsupporting
confidence: 57%
“…The observed effect of inhibition of biofouling in the case of DNDamine coating seems to have the same mechanism as that observed for polycationic polymers -guanidine derivatives, which are known antiseptic agents [42][43][44]. In the case of the latter, close contact of a substance with a high density of positively charged groups with cell walls…”
Section: Discussionsupporting
confidence: 57%
“…AD-L@Ag(0) as a combination therapy: bactericidal, biolminhibitory, biolm-eradicatory Antibiotics that are highly active against Gram-negative bacteria are usually found to be less toxic to Gram-positive bacteria. 96 In this study, we have shown that the AD-L@Ag(0) gel has similar antibacterial and anti-biolm properties against Gram-positive and Gram-negative isolates. The zeta potential evaluated for Ag(0) in the AD-L@Ag(0) gel carries positive charge (+30.2 mV).…”
Section: Biocompatibility and In Vivo Proof-of-conceptmentioning
confidence: 71%
“…Chlorhexidine is an organic compound derived from guanidine; it has bacteriostatic effects at low concentrations and bactericidal effects at high concentrations. 69 This compound is one of the most commonly used disinfectants in handwash preparations, oral gels and liquids, and vaginal preparations. Chlorhexidine is a bisbiguanide (two bound biguanides); hence, it is difficult to dissolve in water, but it easily dissolves in alcohols.…”
Section: Compounds With Disinfectant Propertiesmentioning
confidence: 99%